2023
DOI: 10.1186/s12888-023-04728-6
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala signal abnormality and cognitive impairment in drug-naïve schizophrenia

Abstract: Background Recently studies had showed that the amygdala may take part in the cognitive impairment in schizophrenia (SC). However, the mechanism is still unclear, so we explored the relationship between the amygdala resting state magnetic resonance imaging (rsMRI) signal and cognitive function, to provide a reference for the follow-up study. Methods We collected 59 drug-naïve SCs and 46 healthy controls (HCs) from the Third People’s Hospital of Fos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The fALFF analysis was conducted following a previously established methodology ( 23 ). Essentially, the energy of each frequency within the low-frequency range (0.01 Hz < f < 0.1 Hz) was divided by the energy of each frequency across the entire frequency range to calculate the fALFF value for each voxel.…”
Section: Methodsmentioning
confidence: 99%
“…The fALFF analysis was conducted following a previously established methodology ( 23 ). Essentially, the energy of each frequency within the low-frequency range (0.01 Hz < f < 0.1 Hz) was divided by the energy of each frequency across the entire frequency range to calculate the fALFF value for each voxel.…”
Section: Methodsmentioning
confidence: 99%
“…MRI scanning parameters of resting brain function: TR = 2000 ms, TE = 30 ms, FA = 90º, FOV = 240 mm*240 mm, matrix = 64*64, layer thickness = 4 mm, number of layers = 36, layer spacing = 1 mm, Continuous collection of 250 time point data. Like our previous research [ 13 , 17 ], SPM8 ( http://www.fil.ion.ucl.ac.uk/spm ), cat12 ( http://www.neuro.uni-jena.de/cat12 ), and the Data Processing Assistant for Resting-State fMRI DPARSF ( http://rfmri.org/dpabi ) software were used to preprocess MRI data. Brain structure MRI data were mainly used to measure the volume of amygdala gray matter (calculated according to the Automated Anatomical Labeling (AAL) atlas [ 18 ]).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, some studies had also shown that there were structural and functional abnormalities in the amygdala in SC, such as a decrease in the volume of the amygdala and a reduction in neuronal activity [ 2 , 13 , 14 ]. These abnormalities might be related to the occurrence and manifestation of SC.…”
Section: Introductionmentioning
confidence: 99%
“…Studies utilizing resting state functional MRI studies have identified disturbances in the amygdala’s functional connectivity with other cerebral regions ( 20 23 ). Such structural and functional anomalies contribute to cognitive deficits in schizophrenia ( 24 , 25 ). Therefore, the disrupted amygdala connectivity may serve as a potential trigger for schizophrenia, and its intensive study contributes to our understanding of the pathophysiological mechanisms of schizophrenia ( 26 ).…”
Section: Introductionmentioning
confidence: 99%